Upregulation of Circulating MiR-21 Expression as a Potential Biomarker for Therapeutic Monitoring and Clinical Outcome in Breast Cancer - Anwar, Sumadi Lukman (Asian Pac J Cancer Prev, 2019)
BACKGROUND: Aberrant patterns of microRNA expression have been highlighted as a potential clinical biomarker in breast cancer as the most frequent cancer among women that contributes nearly a quarter of total cancer incidence in 2018. Upregulation of microRNA-21 (miR-21) is associated with adverse clinical outcomes in breast cancer. However, the use of circulating free miR-21 as a non-invasive biomarker for diagnosis and therapeutic monitoring in breast cancer is not well established. We quantified the levels of circulating miR-21 expression and analyzed their correlation with clinicopathological variables and progression-free survival. MATERIALS AND METHODS: This initial study included a cohort of 102 breast cancer patients of different subtypes and clinicat stages. We also included 15 unrelated healthy women. Venous blood from patients was collected at diagnosis and after treatment of surgery and chemotherapy. MiR-21 expression was quantified from total RNA fraction isolated from patient’s plasma. Quantitative reverse transcription polymerase chain reaction (qRT-PCR) was used to analyzed miR-21 expression. RESULTS: Expression of circulating miR-21 was significantly elevated in breast cancer patients compared to healthy women (median miR-21 expression levels were 7.67±2.2 and 1.28±0.16, respectively; p<0.0001). Significant reduction of miR-21 expression was observed in breast cancer patients after completion of surgery and chemotherapy (median miR-21 expression levels were 7.67±2.2 at diagnosis and 2.16±1.28 after treatment, respectively; p<0.0001). MiR-21 expression was higher in breast cancer patients younger than 40-year-old but was not significantly different according to different histopathological grades and clinical stages at diagnosis. Patients with upregulation of circulating miR-21 were associated with poor progression-free survival (median survival 72 vs 86 weeks, respectively; log-rank (Mantel-Cox) test, p=0.049). CONCLUSION: MiR-21 expression was upregulated in breast cancer patients and might serve as a therapeutic monitoring marker.